Modernisation of public sector financial reporting systems in Europe: Challenges and milestones - Michal Svoboda (European Financial and Accounting Journal, 2016)
Many European countries have been carried out a modernization projects in public sector financial reporting since the last two decades. Consequence of a stronger demand for complex, reliable and relevant economic information on government is governments' efforts towards better accountability. IPSAS standards, a full accrual national financial reporting standards closed to, or national standards with clear reference to IPSAS, are often considered as the best tool for that. This article aims to identify key challenges and milestones - four key aspects of these public sector financial reporting modernization projects. It offers a comparison amongst several European countries comparing the ways these countries decided to deal with those challenges and milestones.
Keywords: H83; M41; M42; M48; 650; Governmental Accounting; IFRS; IPSAS; Public sector